An Expeditious Ultrasound-Initiated Green Synthesis of 1,2,4-Thiadiazoles in Water - Chauhan S.; Verma P.; Mishra A.; Srivastava V. (My University, 2025)
[Figure not available: see fulltext.] A convenient, environmentally benign, metal- and catalyst-free protocol has been developed for the conversion of thioamides to the corresponding 1,2,4-thiadiazole derivatives with chloranil under ultrasound irradiation in water at room temperature. This paper describes a general procedure for the synthesis of different 1,2,4-thiadiazoles in excellent yield in short reaction time via sonochemistry. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.